Penyuluhan Edukatif: Manajemen Emosional Spiritual Perspektif Islam dan Penerapannya: Pengabdian - Siti Uswatun Khasanah; Marhamah; Ishak Syahroji; Madian; Diniel Abrar (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Emotional intelligence (EQ) and spiritual intelligence (SQ) are two intelligences that play a crucial role in shaping a complete human personality according to Islam. The International Community Service Program (PKM) between the Islamic University of Jakarta and the Muhammadiyah Turkiye Branch aims to increase public understanding regarding emotional and spiritual management according to Islamic guidance. The implementation method consisted of educational counseling, discussions, and a Q&A session via webinars attended by Indonesian migrant workers in Turkiye, schoolchildren, and parents in Indonesia. The results of the activity demonstrated an increase in participants' awareness and ability to manage negative emotions and a strengthening of spiritual practices such as prayer, dhikr (remembrance of God), reading the Quran, and practicing the values of faith and piety. The four aspects of SQ development emphasized in Islam are al-Qalb (the heart), al-Ruh (spirit), an-Nafs (the soul), and al-Aql (the mind). Thus, this activity contributed to strengthening the character and psychological stability of participants in facing life's challenges.